2020
DOI: 10.21613/gorm.2019.946
|View full text |Cite
|
Sign up to set email alerts
|

Is There An Association Between Kisspeptin Levels And Gestational Diabetes Mellitus?

Abstract: <p><strong>Objective:</strong> To find out the relationship of maternal serum levels of kisspeptin with gestational diabetes mellitus status.</p><p><strong>Study Design:</strong> A total of 158 pregnant women between 24 and 28 weeks of gestation were divided into two groups according to gestational diabetes mellitus status: (i) Pregnant women with gestational diabetes mellitus (gestational diabetes mellitus group, n=76) and (ii) Healthy pregnant women (control group, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Clinical observations have indicated that kisspeptin concentration in GDM women is lower both in the second and third trimester of pregnancy compared to those without GDM (second trimester: 4.51 ± 3.18 (GDM) vs. 10.33 ± 2.65 (controls) nmol/L; third trimester: 11.64 ± 7.65 (GDM) vs. 20.48 ± 7.60 (controls) nmol/L) [ 68 ]. These results are contrary to those obtained by Arslan et al, who have shown no differences in the kisspeptin levels in women with GDM and healthy ones [ 67 ]. A different research methodology could partially explain distinctions among the obtained results.…”
Section: Role Of Kisspeptin In Gestational Diabetes Mellitus—a Placen...contrasting
confidence: 99%
See 1 more Smart Citation
“…Clinical observations have indicated that kisspeptin concentration in GDM women is lower both in the second and third trimester of pregnancy compared to those without GDM (second trimester: 4.51 ± 3.18 (GDM) vs. 10.33 ± 2.65 (controls) nmol/L; third trimester: 11.64 ± 7.65 (GDM) vs. 20.48 ± 7.60 (controls) nmol/L) [ 68 ]. These results are contrary to those obtained by Arslan et al, who have shown no differences in the kisspeptin levels in women with GDM and healthy ones [ 67 ]. A different research methodology could partially explain distinctions among the obtained results.…”
Section: Role Of Kisspeptin In Gestational Diabetes Mellitus—a Placen...contrasting
confidence: 99%
“…The available data that analyzed changes in kisspeptin levels in patients with GDM compared to healthy pregnant women are limited to only a few clinical studies [ 10 , 11 , 64 , 67 , 68 , 69 ]. It has been reported that women with GDM had significantly lower plasma kisspeptin levels compared to healthy ones [ 64 ].…”
Section: Role Of Kisspeptin In Gestational Diabetes Mellitus—a Placen...mentioning
confidence: 99%
“…We observed no significant differences in gestation-specific kisspeptin levels in pregnancies affected by GDM; however, the gestation adjusted kisspeptin levels from all trimesters were lower than in control pregnancies. Previous data thus far are inconclusive, with 2 studies reporting lower second- and third-trimester plasma kisspeptin levels in women with GDM than in controls ( 15 , 23 ), while another reported no differences ( 56 ). Nonetheless, kisspeptin has been proposed to play a significant role in beta-cell adaptation to the pregnant state ( 23 ).…”
Section: Discussionmentioning
confidence: 96%
“…Kisspeptin concentrations decreased in pregnant women at 16-20 gestational weeks who had placentovascular pathologies, including preeclampsia and intrauterine growth restriction 27 . Cetovic et al 28 also reported markedly lower kisspeptin concentrations in pregnant women with type 1 diabetes, gestational diabetes, and gestational hypertensive disorders, despite other studies demonstrating opposing findings 29 . In another study, serum kisspeptin concentrations in the first trimester were lower in pregnant women who subsequently developed small-for-gestational-age fetuses 30 .…”
Section: Discussionmentioning
confidence: 95%